Peran Stakeholders Dalam Pengembangan Kelompok Tani Ngudi Utomo Di Desa Karangasem Kabupaten Klaten - Rizky Jimi Wijaya; Suminah; Suwarto (CV. Multi Kreasi Media, 2023)
The Ngudi Utomo farmer group is one of the farmer groups in Karangasem Village, Cawas District, Klaten Regency. In the running of farmer groups, it is necessary to involve the role of each stakeholder to assist in the development of farmer groups. The role of stakeholders will affect the development of farmer groups such as the developments undertaken by farming and the participation of members of farmer groups. This study aims to reveal the role of stakeholders in the development of farmer groups and the impacts that arise in the development of farmer groups, namely the roles of policy creators, coordinators, facilitators, implementers, and accelerators. This research uses a qualitative basic method with a descriptive approach and uses a case study research design. The research location is in Karangasem Village, especially the Ngudi Utomo Farmer Group. Determination of informants was carried out by purposive sampling with key informants and snowball sampling technique, namely 8 informants in total. Data validity uses source triangulation. The results showed: Cooperation between stakeholders in the development of the Ngudi Utomo farmer group in Karangasem Village has been going well but the role has not been maximized. This can be seen where each stakeholder gives their respective roles in supporting the development of the Ngudi Utomo Farmer Group.